Business Strategies for Carbon Fiber-reinforced Polymer Recycling in the Aviation Industry: A Literature Review - Naim, Arshi; Khan, Shad Ahmad; Malik, Praveen Kumar; Juju, Undang (Indonesian Journal of Sustainability Accounting and Management, 2024)
This study investigates business management strategies to enhance the effectiveness and longevity of CFRP-Cs applications in the aviation industry. In the current scenario, the transport industry has increasingly turned to lightweight materials for external structures. The automobile, aviation, and train sectors are particularly keen on utilizing Carbon Fiber-Reinforced Polymers (CFRPs) due to their lightweight nature, erosion resistance, and various functional elements beneficial for the transport industry (Bonfanti et al., 2023). However, CFRP composites (CFRP-Cs) pose challenges in the recycling process due to their compounds. The recycling process can only be conducted under extreme conditions, and direct reuse of these CFRP-Cs is difficult to process. A systematic literature review is conducted to examine the use and state of the art of CFRP fibers, the recycling processes adopted, and their associated challenges, benefits, and guidelines. The existing state of the art suggests that the use of CFRP cannot be avoided. However, for environmental sustainability, business strategies should focus on creating a market for CFRP recycling (Deng et al., 2020) and fostering consensus for the progressive use of recycled materials across industries. This involves developing guidelines within a sliding directive to ensure the necessary mechanical performance of CFRP-Cs while promoting environmental responsibility.